Efektifitas Guided Imagery Dan Slow Deep Breathing Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Di Desa Prigi Purbalingga - Maryoto, Madyo; Pramudya Wardhani, Putri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Hypertension is a condition where the blood pressure in the arteries is too high. Hypertension occurs due to excessive workload of the heart when pumping blood throughout the body to meet the needs of oxygen and nutrients by the body. Hypertension is the leading cause of death which is often referred to as the silent killer disease. Nonpharmacological therapies used to reduce blood pressure in people with hypertension include Guided Imagery and Slow Deep Breathing therapy. This case study aims to describe the application of Guided Imagery and Slow Deep Breathing to lower blood pressure in families whose family members have hypertension in Prigi Purbalingga Village. The case study was conducted by observation for three meetings and the intervention of providing Guided Imagery and Slow Deep Breathing for three days on October 22-24, 2024. The results of the case study of the application of Guided Imagery and Slow Deep Breathing on the first day the patient was still in the category of grade 2 hypertension with blood pressure 162/102 mmHg, on the second day there was a decrease to the category of grade 1 hypertension with blood pressure 134/96 mmHg, and on the third day to pre-hypertension with blood pressure 120/80 mmHg. In conclusion, Guided Imagery therapy and Slow Deep Breathing can significantly reduce blood pressure in people with hypertension.